Supply Chain Architecture: A Blueprint for Networking the Flow of Material, Information, and Cash - Walker, William (CRC Press, 2009)
Supply Chain Architecture: A Blueprint for Networking the Flow of Material, Information, and Cash applies five crucial business principles to solve network problems for geographically separated workers who must team together to deliver products and services.